PELAKSANAAN PROGRAM PENGEMBANGAN INTELEKTUAL BAGI SISWA DI ASRAMA MAN 2 BOYOLALI - M Ghofar Ismail; Siti Khoiriyah (Universitas Wahid Hasyim Semarang, 2020)
Abstract The purpose of this study was to determine the implementation of intellectual development programs for students in the dormitory of MAN 2 Boyolali. This research used a qualitative descriptive approach which was conducted in March-June 2017 at the MAN 2 Boyolali Dormitory. Collecting data using the method of observation, interviews and documentation. The results of this study can be concluded as follows: (1) The implementation of the intellectual development program is carried out for boarding students of MAN 2 Boyolali. (2) Types of intellectual development programs: Foreign language development through Muhadhoroh, FTMP, General Sciences. (3) Using modern constructivist intellectual development methods, CTL, GLC, in addition to modern methods equipped with modern media to keep up with the times and supporting infrastructure (4) For example, at FTMP, students are asked to find and present a short story, and make short stories , making articles, opinions, editing a work, then exposing it on the internet and looking for many who comment or comment, write poetry, fiction and non-fiction, what stands out is scientific writing, until students in the dormitory win the writing of high school level scientific papers in Boyolali district. So that students in the dormitory in carrying out scientific papers are not so difficult. The implementation of intellectual development programs for students in dormitories has a positive effect on MAN 2 Boyolali. Keywords : Intellectual Development Program, Students, Dormitories Abstrak Tujuan penelitian ini adalah untuk mengetahui pelaksanaan program pengembangan intelektual bagi siswa di asrama MAN 2 Boyolali. Penelitian ini menggunakan pendekatan deskriptif kualitatif yang dilaksanakan pada bulan maret-juni 2017 di Asrama MAN 2 Boyolali. Pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Hasil penelitian ini dapat disimpulkan sebagai berikut: (1) Pelaksanaan program pengembangan intelektual dilaksanakan untuk siswa asrama MAN 2 Boyolali. (2) Jenis-jenis program pengembangan intelektual: Pengembangan Bahasa asing melalui muhadhoroh, FTMP, Ilmu Umum. (3) Menggunakan metode pengembangan intelektual secara modern konstruktivisme, CTL, GLC, selain metode modern dilengkapi dengan media yang modern demi mengikuti perkembangan zaman dan sarana prasarana yang mendukung (4) Misalkan pada FTMP, siswa disuruh mencari dan mempresentasikan suatu cerpen, dan membuat cerpen, membuat artikel, opini, mengedit suatu karya, lalu mengekspos di internet dan mencari banyak yang mengkomen atau mengelike, menulis puisi, fiksi dan non fiksi, yang menonjol adalah karya tulis ilmiah, hingga siswa di asrama menjuarai penulisan karya ilmiah tingkat SMA satu kabupaten Boyolali. Sehingga siswa di asrama dalam mengerjalan karya tulis ilmiah tak begitu kesulitan. Pelaksanaan program pengembangan intelektual bagi siswa di asrama berpengaruh positif untuk MAN 2 Boyolali. Kata kunci : Program Pengembangan Intelektual, Siswa, Asrama